Journey of Dhropadi Music Pakhawaj Haveli to Gharana - Paul, Kumud Ranjan (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Pakhawaj is a percussion Musical instrument, which is included in North Indian classical Music. There are two divisions of North Indian Sangeet Parampara (Music Tradition). The first one is 'Sompradaya' - parompara and the second one is 'Darbari' Parampara. 'Sompradaya' parampara was religious. It was temple oriented as well it was for non-professional musicians. 'Darbari' parampara was secular. It was oriented for professional musicians like professional court musician and professional caste musician. From generations and disciples of those professional court musicians and professional caste musicians, the Gharana system was started approximately from 18th century, in North Indian Classical Music. I try to discuss about parampara, Sampraday as well as Gharana. I also discuss here the named of different paramparas Gharanas of Pakhawaj. Mathura Parampara (Braja Mondal Parampara) which was religious or Haveli Parampara of Pakhwaj.